Fermentation of cellulose pyrolysis oil by a Clostridial bacterium. (December 2020) - Buendia-Kandia, F.; Greenhalf, C.; Barbiero, C.; Guedon, E.; Briens, C.; Berruti, F.; Dufour, A.
Abstract: The coupling of thermochemical and biological conversion of biomass is a promising strategy to produce chemicals in future integrated biorefineries. Indeed, thermochemical conversion such as pyrolysis is a fast process without any solvent or enzyme for the depolymerisation of biomass. In this work, cellulose was pyrolyzed to produce sugars which have been then fermented by bacteria ( Clostridium acetobutylicum ) to produce acetone and butanol. This type of bacteria presents an interesting biological platform: it is resilient, easily up-scalable and Clostridium can be genetically engineered to target various other chemicals. Pyrolysis of cellulose was performed in a continuous fluidized bed reactor equipped with a staged condensation system, including a warm electrostatic precipitator. Different bio-oil fractions rich in levoglucosan (LVG) and with different concentrations in inhibitors for the fermentation stage were produced. LVG was found to be non-fermentable by C. acetobutylicum . Therefore, the bio-oil fractions were hydrolysed to obtain fermentable glucose. The mechanisms of acid hydrolysis (with diluted H2 SO4 ) of LVG and cellobiosan have been revealed by high resolution mass spectrometry. The microorganisms were not able to grow with all hydrolysed bio-oil fractions depending on the concentration in inhibitors (aldehydes and organic acids). The fractions rich in LVG (and then glucose) lead to normal bacterial growth and normal fermentation products pattern without the need of detoxification. These results show the importance of a pyrolysis process with a staged condensation as a preliminary step for fermentation. It opens the road to production of various cellulose-derived chemicals by bacteria. Graphical abstract: Image 1 Highlights: Cellulose was depolymerized by fast pyrolysis. Bio-oil fractions rich in levoglucosan (LVG) were produced by staged condensation. LVG was not metabolized by Clostridium Acetobutylicum . Mild acid hydrolysis of LVG in bio-oils was fast and selective. Hydrolysed bio-oils were fermented by Clostridium Acetobutylicum.